Atlas of travel and tourism development - Shackley, Myra L (Elsevier, 2015)
From travel in the ancient and classical world to the growth of underwater tourism in the Great Barrier Reef and the influence of the Gulf War on regional tourism, the Atlas of Travel and Tourism Development is a new departure from conventional texts, providing a unique overview of the growth of the tourism industry. Divided into three sections, the text looks first at the past, examining the influence of global geography on travel patterns, and provides an overview of the history of travel and tourism. It then moves onto the present, using a regional framework to demonstrate how the physical and historical geography of each area is related to tourism development. The final section provides a forecast of future trends for the next two decades. * A unique pictorial history of global travel and exploration * Easy-to-use maps that chart development of tourism * Explains the growth of tourism destinations and trends in a geographic and historic global context.